Isu kesetaraan laki-laki dan perempuan dalam perspektif Al-Qur’an dan Hadits - El Syafi, Rachmi Dwi Wiladatil Qodliyah; Hasibuan, M. Surya; Said, Umar; Nafisa, Hanna; Setia, Nadzivatul Mar’ati; Syarifah, Siti Lailatusy (Maliki Interdisciplinary Journal, 2025)
Equality between men and women is an essential concept in Islam, as found in the Quran and Hadith. This study aims to explore Islamic perspectives on gender equality by reviewing Quranic verses and various hadiths that emphasize the rights and responsibilities of both genders. The Quran highlights justice and the recognition of women’s significant roles in society. The Hadiths of Prophet Muhammad (peace be upon him) also provide concrete examples of fair treatment towards women and acknowledgment of their contributions to social life. Through this analysis, it is hoped that readers will understand that Islam supports gender equality and encourages the implementation of these principles in daily life.